Aberrant integration of Hepatitis B virus DNA promotes major restructuring of human hepatocellular carcinoma genome architecture - Eva G. Álvarez (Nature Portfolio, 2021)
Hepatitis B virus (HBV) infection and DNA integration is a frequent cause of hepatocellular carcinoma (HCC), but the consequences of this process are not fully understood. Here the authors use whole-genome and long-read sequencing data from HCC patient samples to study the timing and alterations induced by HBV insertions.